Penguatan Kesadaran Masyarakat terhadap Risiko Banjir dan Dampaknya pada Sektor Ekonomi Lokal di Tapanuli Tengah dan Aceh - Harkim Harkim; Bambang Sugiharto; Rejekia V Simanungkalit; Maya Andriani; Egy Juwita Tarigan (Universitas Pahlawan Tuanku Tambusai, 2026)
Flooding is one of the natural disasters that frequently occurs in the regions of Central Tapanuli and Aceh, causing not only physical damage but also significant impacts on the local economy. The low level of public awareness regarding flood risks, along with limited knowledge of its economic impacts, remains a major challenge in mitigation efforts. This community service activity aims to enhance public awareness and understanding of flood risks and their economic consequences. The methods used include participatory socialization, educational outreach, focus group discussions, and community-based assistance. The activity involves affected communities, village officials, and local business actors. The results indicate an improvement in community understanding and the emergence of awareness to implement simple mitigation measures and economic adaptation strategies, thereby strengthening community economic resilience in a sustainable manner.